ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SMP KELAS VII PADA SOAL-SOAL PERSAMAAN DAN PERTIDAKSAMAAN LINEAR SATU VARIABEL - Yulianti - Yulianti; Yunita Eka Purnama; Wahyu - Hidayat (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
The purpose of this research is to describe and analyze the difficulties of students in solving problems of mathematics communication skills of students of grade VII SMP Darul Hikmah regarding the material of linear equations and inequalities of one variable. The data analysis technique uses descriptive methods, namely analyzing data by describing or describing the data that has been collected. The population of SMP Darul Hikmah students is 26 students. The data were obtained through test techniques using instruments, amounting to 4 questions and designed in the form of a description (essay) as an indicator to measure the level of communication skills. From the results of the calculation of the 4 indicators, namely indicators of organizing and combining mathematical thinking of 75.96%, indicators of analyzing and evaluating mathematical thinking of 83.65%, indicators using mathematical language to express correctly by 44.23%, indicators of communicating mathematical thinking logically and clearly so that it is easy to understand at 12.50%. Based on these data, junior high school students' mathematical communication skills are still in the low category, namely 54% and need improvement.